The effectiveness of dragon fruit peel Hylocereus polyrhizus in feed on color quality and growth performance of comet fish Carassius auratus - Yuli Andriani; Shela Rihadatul Nabila; Rusky Intan Pratama; Fittrie Meyllianawaty Pratiwy; In In Hanidah (Jurnal Akuakultur Indonesia)
Color is a defining trait of ornamental fish, crucial for their aesthetic appeal, but it diminishes without pigment supplementation in their diet. Utilizing dragon fruit skin as a natural feed constituent offers a promising method to intensify fish coloration. This investigation aims to assess the impact of incorporating dragon fruit skin meal into fish feed on color vibrancy and growth performance, specifically focusing on comet fish. The test subjects, ranging from 4 to 6 cm in size and weighing 3.1 ± 0.2 grams, underwent examination. Employing a completely randomized design (CRD), the study involved four treatments replicated four times: treatment A (control), B (5% dragon fruit skin meal addition), C (10% addition), and D (15% addition). Before commencing the study, a preliminary assessment of dragon fruit skin meal was conducted, encompassing a chromameter-based color pigmentation test. Results revealed positive a (red) and b (yellow) values, a chroma value of 26.32 signifying carotenoid pigments, a hue value of 3.18° indicating a red-orange hue, and a moderate antioxidant activity was observed, indicating the presence of antioxidant compounds. Findings demonstrated that a 15% addition of dragon fruit skin meal substantially enhanced color vibrancy across the fish's body sections, including the head, body, and tail. Although fish weight and length were influenced by the feed amendment, ANOVA analysis did not ascertain significant effects. Furthermore, treatment C exhibited the most favorable feed conversion ratio and specific growth rate, recording values of 0.09 ± 0.03 and 0.934 ± 0.215, respectively.